Effect of fiber and solenoid variation parameters on the elements of a corrector PID for electromagnetic fiber squeezer based polarization controller - Abdallah Zahidi; Amrane said; Nawfel Azami; Naoual Nasser (Institute of Advanced Engineering and Science, 2020)
Controlling the polarization of the light output from single-mode fiber systems is very important for connecting it to polarization-dependent integrated optical circuits, while applications using a heterodyne detection system. Polarization controller using fiber squeezer is attractive for a low-loss, low-penalty coherent optical fiber trunk system. However, for polarization controllers using electromagnetic fiber squeezer, the stability problem due to the saturation of their magnetic circuit must be studied. In fact, in their conventional configuration, open-loop stability affects performance and limits applications. First at all, this effect has been analyzed and a feedback circuit with correctors has been proposed to improve stability performance. Then a simulation study is proposed to examine the influence of the system parameters on the corrector constants. The results of the simulation show that if the system parameters change the constants Kp, Ki and Kd of the PID corrector must be adjusted to keep an optimized dynamic response.